2021
DOI: 10.1016/j.heliyon.2021.e06669
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of durian fruit rind polysaccharide gel encapsulated prebiotic and probiotic dietary supplements on growth performance, immune-related gene expression, and disease resistance in Zebrafish (Danio rerio)

Abstract: The present study investigated the effect of polysaccharide gel (PG) extracted from the rind of durian fruit which is encapsulated with Bacillus subtilis as a feed and co-inoculation with Artemia nauplii in the induction of immune response in Danio rerio after Vibrio immersion challenge (5 days). The total RBC count, lysozyme activity test, weight, and length analysis revealed that the zebra fishes fed with the PG encap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(43 reference statements)
1
6
0
Order By: Relevance
“…To our knowledge, no report is available on the use of probiotics La or Lb in combination with mushroom extract as a synbiotic formulation compound in farmed fishes. However, the beneficial effects of the synbiotic formulation on zebrafish performance parameters including weight gain percentage, SGR FCR, and survival are in agreement with previous studies ( Safari et al, 2018 ; Mohammadian et al, 2019 ; Priya et al, 2021 ). For example, a similar improvement in the growth performances was observed in a study with a commercial synbiotic that comprised of a probiotic Entercoccus faecium and fructooligosaccharide as a prebiotic in zebrafish ( Nekoubin et al, 2012b ).…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, no report is available on the use of probiotics La or Lb in combination with mushroom extract as a synbiotic formulation compound in farmed fishes. However, the beneficial effects of the synbiotic formulation on zebrafish performance parameters including weight gain percentage, SGR FCR, and survival are in agreement with previous studies ( Safari et al, 2018 ; Mohammadian et al, 2019 ; Priya et al, 2021 ). For example, a similar improvement in the growth performances was observed in a study with a commercial synbiotic that comprised of a probiotic Entercoccus faecium and fructooligosaccharide as a prebiotic in zebrafish ( Nekoubin et al, 2012b ).…”
Section: Discussionsupporting
confidence: 92%
“…The results agreed with the study of Mohammadi et al [47], which reported resistance against A. hydrophila of Nile tilapia-fed diets added with polysaccharide derived from Pistacia vera hulls at 2.5, 5, and 10 g/kg were higher than fish fed a diet without polysaccharide. Priya et al [16] also evaluated the efficacy of a polysaccharide extracted from durian rind on disease resistance against Vibrio anguillarum in Zebrafish (Danio rerio). The fish fed with the polysaccharide encapsulated with Bacillus subtilis had a higher survival rate than the non-polysaccharide encapsulated group after 5 days of the Vibrio immersion challenge.…”
Section: Antibacterial Propertymentioning
confidence: 99%
“…Moreover, polysaccharide also has immunomodulating properties. For instance, polysaccharide gel (PG) extracted from D. zibethinus could improve prophenoloxidase activity in black tiger shrimp (Penaeus monodon) [49], increasing immune-related genes such as interleukin 1 beta (Il1b), lysozyme (lyz), tumor necrosis factor-alpha (TNF-α), superoxide dismutase (SOD) genes in Zebrafish (D. rerio) [16]. In addition, the minerals, including magnesium, manganese, and copper, were elevated in fish-fed diets supplemented with durian rind and may improve immune response, resulting in higher survival rates than the control.…”
Section: Antibacterial Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with this idea many studies are being conducted. For instance, addition of QQ enzymes into the rearing water or bio encapsulating them in the feedstock have been successfully demonstrated to control aquatic pathogens 140–146 . The use of AHL‐degrading marine bacteria and their purified QQ enzymes has been successful in lowering or eliminating pathogenic bacteria's pathogenicity against fish, crustaceans, molluscs and corals to date.…”
Section: Perspectivementioning
confidence: 99%